2022
DOI: 10.3390/su141811248
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Perceived Usefulness, Reliability, and COVID-19 Pandemic on Digital Banking Effectiveness: Analysis Using Technology Acceptance Model

Abstract: This study examined the digital banking effectiveness of a bank. This study specifically explored the effect of perceived usefulness, banking system reliability, and COVID-19 pandemic on the digital banking effectiveness of a bank in Malaysia based on the technology acceptance model (TAM). Data collection was undertaken using a questionnaire survey involving 228 clients of the bank. The findings indicated that two of the chosen factors, namely, perceived usefulness and reliability of the banking system, signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…In addition, perceived usefulness influences individual attitudes toward the intention to utilize mobile banking (Y.-K. Lee, Park, Chung, & Blakeney, 2012). This study applies the TAM model and found perceived usefulness essential in encouraging customers to use more online channels to conduct their transactions and obtain product information (Ghani, Ali, Musa, & Omonov, 2022;Larasetiati & Ali, 2019). Thus, perceived usefulness also significantly influences client attitudes, in addition to having an impact on their intention to use web banking (Yadav, Chauhan, & Pathak, 2015).…”
Section: Perceived Usefulness and Attitude Towards Using M-bankingmentioning
confidence: 91%
“…In addition, perceived usefulness influences individual attitudes toward the intention to utilize mobile banking (Y.-K. Lee, Park, Chung, & Blakeney, 2012). This study applies the TAM model and found perceived usefulness essential in encouraging customers to use more online channels to conduct their transactions and obtain product information (Ghani, Ali, Musa, & Omonov, 2022;Larasetiati & Ali, 2019). Thus, perceived usefulness also significantly influences client attitudes, in addition to having an impact on their intention to use web banking (Yadav, Chauhan, & Pathak, 2015).…”
Section: Perceived Usefulness and Attitude Towards Using M-bankingmentioning
confidence: 91%
“…Perceived immediate use advantages (i.e., perceived gains) and perceived sacrifices (i.e., perceived losses) are the antecedent variables of perceived cost [ 38 ]. Some scholars have also used factors such as perceived risk, cost of purchase, quality of service, and the quality of the product as antecedent variables affecting the consumers’ perceived value (Wood and Scheer, 1996; Zhong, K., 2013) [ 39 ]. Regarding the elements impacting the customer’s perceived value, we introduced two achievable variables to the technology acceptance model: perceived cost (B3) and personal motivation (B4) [ 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…In this case, digital financial services are the logical choice needed to improve the operations and cost efficiency of banks, particualry amoing the so-called millennials cohort of customers (Windasari, Kusumawati, Larasati, & Amelia, 2022). The effectiveness and efficiency of digital banking services are felt to provide many benefits and aid the millennial generation in meeting financial transaction needs, such as online shopping, credit purchases, and interbank transfers (Ghani et al, 2022). The digitalization of services can also help to close the service gap between banks and the community, more efficient, faster, and cost-effective, which is highly favored by the millennial generation (Ji, Wang, Xu, & Li, 2021).…”
Section: Digital Banking Servicesmentioning
confidence: 99%
“…Previous literature has summarized the effort of the coronavirus pandemic in changes in the structure of the world's Islamic banking services (Abbas A & Ayu Frihatni A, 2020;Cahyono, Rani, & Mardianto, 2021;Hassan, Rabbani, Asad, & Ali, 2020;Mansour, Ajmi, & Saci, 2022;Rabbani, Asad, et al, 2021;Rabbani, Bashar, et al, 2021). Customers are currently highly dependent on digital banking services, especially in a situation where the potential for transmission of the COVID-19 virus still exists (Banna, Hassan, Ahmad, & Alam, 2022;Ghani, Ali, Musa, & Omonov, 2022). The preliminary study results also revealed that there had been much research on the effect of post-COVID-19 Islamic banking digital services on customer satisfaction (Fida, Ahmed, Al-Balushi, & Singh, 2020;Thaker, Amin, & Pitchay, 2019;Zouari & Abdelhedi, 2021b).…”
Section: Introductionmentioning
confidence: 99%